2015
DOI: 10.1186/s12936-015-0815-z
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of culture conditions for long-term in vitro culture of Plasmodium vivax

Abstract: BackgroundThe study of the biology, transmission and pathogenesis of Plasmodium vivax is hindered due to the lack of a robustly propagating, continuous culture of this parasite. The current culture system for P. vivax parasites still suffered from consistency and difficulties in long-term maintenance of parasites in culture and for providing sufficient biological materials for studying parasite biology. Therefore, further improvement of culture conditions for P. vivax is needed.MethodsClinical samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 21 publications
2
62
0
1
Order By: Relevance
“…Many culture medium formulations have been reported for the ex vivo maturation of P. vivax (4,7,18,19). Most current formulations are based on McCoy's 5A medium with human serum added with or without additional supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Many culture medium formulations have been reported for the ex vivo maturation of P. vivax (4,7,18,19). Most current formulations are based on McCoy's 5A medium with human serum added with or without additional supplements.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated robust invasion assay which has allowed testing molecules in invasion of 2C3 as the monoclonal antibody of DARC for blocked PvDBP interaction by short term P. vivax invasion process 13 . An invasion mechanism study of P. vivax faces a considerable hurdle owing to the inability to continuously culture the parasites in vitro 14 15 . To overcome these problems, we consider evidence from homologous protein families in other Plasmodium spp.…”
mentioning
confidence: 99%
“…While there have been some recent improvements to in vitro culture techniques for Plasmodium vivax, the culture of this parasite is still limited by the requirement of reticulocytes, and the parasite density over longterm culture is low (7). However, the recent adaptation of the zoonotic malaria species Plasmodium knowlesi (8) to continuous in vitro culture in human erythrocytes (9)(10)(11) has changed this position.…”
mentioning
confidence: 99%